Induction of Tolerance to Cardiac Allografts Using Donor Splenocytes Engineered to Display on Their Surface an Exogenous FasL Protein - Yolcu, Esma S. (2008)
The critical role played by FasL in immune homeostasis renders this molecule as an attractive target for immunomodulation to achieve tolerance to auto and transplantation antigens. Immunomodulation with genetically modified cells expressing FasL was shown to induce tolerance to alloantigens. However, genetic modification of primary cells in a rapid, efficient, and clinically applicable manner proved challenging. Therefore, we tested the efficacy of donor splenocytes rapidly and efficiently engineered to display on their surface a chimeric form of FasL protein (SA-FasL) for tolerance induction to cardiac allografts. Intraperitoneal injection of ACI rats with WF splenocytes displaying SA-FasL on their surface resulted in tolerance to donor, but not F344 third party, cardiac allografts. Tolerance was associated with apoptosis of donor reactive T effector cells and induction/expansion of CD4(+)CD25(+)FoxP3(+) T regulatory (Treg) cells. Treg cells played a critical role in the observed tolerance as adoptive transfer of sorted Treg cells from long-term graft recipients into naïve unmanipulated ACI rats resulted in indefinite survival of secondary WF grafts. Immunomodulation with allogeneic cells rapidly and efficiently engineered to display on their surface SA-FasL protein provides an effective and clinically applicable means of cell-based therapy with potential application to regenerative medicine, transplantation, and autoimmunity.